¿Que es el hombre? Un enfoque con la teoria de Szondi - Schopeflocher, Ruth (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
There is a difference between the classical psychoanalytic conception and Szondi’s theory concerning sublimation. According to Freud, our vices are transformed, to a certain extent, into virtues; antisocial tendencies into social. For Szondi, on the other hand, both tendencies are found a priori in the human being. In his three-dimensional drive test, Szondi implies that notions of Good and Evil emanate from the same psychic origin.